Recent Advances and Future Challenges in the Genetics of Multiple Sclerosis - Lill, Christina M. (Frontiers in Neurology, 2014)
Multiple Sclerosis (MS) is the most common auto-inflammatory disease of the central nervous system, affecting more than 2 million individuals worldwide. It is a genetically complex disease, in which a substantial part of a person's liability to develop MS is caused by a combination of multiple genetic and non-genetic (e.g. environmental) risk factors. Increasing this complexity, many of the involved risk factors likely interact in an intricate and hitherto ill-defined fashion. Despite these complexities, and owing greatly to the advent and application of large-scale genome-wide association studies, our understanding of the genetic factors underlying MS etiology has begun to gain unprecedented momentum. In this perspective, I will summarize some recent advances and outline future challenges in MS genetics research.